OGC O03 Patient-derived oesophageal adenocarcinoma organoids may predict response to induction therapies in oesophageal cancer. (7th December 2022) - Bolger, Jarlath; Allen, Jonathan; Radulovich, Nikolina; Ng, Christine; Allison, Frances; Bach, Yvonne; Shathasivam, Premalatha; Tsao, Ming; Elimova, Elena; Darling, Gail; Yeung, Jonathan
Abstract: Background: The current management of locally-advanced oesophageal adenocarcinoma (OAC) includes neoadjuvant therapy; however, there are no robust markers that predict treatment response. While 25% of patients will have a complete pathological response, up to 40% will have little or no response. Identification of this non-responsive subgroup prior to treatment and robust testing with alternative drug panels may help to generate personalised induction regimens. Patient derived organoids have shown some promise in other cancers as a model for personalised therapy. The aim of this study is to determine the feasibility of utilising PDOs to predict response to induction therapy. Methods: PDOs were generated from endoscopic biopsies taken pre-treatment in patients with locally advanced (LA) or metastatic (M) esophageal cancer. For those with LA disease, samples were also taken post-resection. PDOs were established, passaged, then treated with a drug panel of platinum-based drugs, taxane-based drugs, topoisomerase inhibitors and 5-flurouracil. Treatment response curves and growth metrics were mapped back to treatment response, based on pathological tumour regression grade in the LA group and clinical response based on cross-sectional imaging in the M group. Results: 19 organoids from 7 LA tumours[YJ1] [JB2] and 10 organoids from 8 M tumours were treated. For LA PDOs, there were significant correlations between cisplatin IC50 (p=0.007), EC50 (p=0.002) and TRG. There was a correlation between paclitaxel AUC and TRG (p=0.02). For PDOs treated with irinotecan, there was an in-vitro response in 45% of organoids which had no clinical response to induction therapy. None of these patients received a topoisomerase inhibitor in their induction therapy. For PDOs treated with 5-FU, 41% of those with no response to induction therapy showed an in vitro response to treatment. Those organoids showing a response had not received 5-FU as part of induction. For M PDOs, there was a correlation between cisplatin and clinical response for AUC (p=0.04), and a trend for IC50 (p=0.07). There were also correlations between paclitaxel and clinical response for IC50 (p=0.04) and AUC (p=0.01). There were no correlations with irinotecan or 5-FU in this subset. These results raise the possibility that the response of PDOs to drug treatments in vitro may in future be used to develop personalised drug induction regimens for patients with esophageal cancer. Conclusions: Treatment responses of OAC PDOs treated in vitro with standard chemotherapeutic agents may predict clinical response in the corresponding patient's tumor. A PDO model may form the basis for screening therapeutic agents in the neoadjuvant window, allowing the development of truly personalised neoadjuvant strategies. Further in vitro and in vivo testing is warranted to determine how these models may be applied to a clinical context.